A cidade como currículo - Marcelino Neto, Eduardo dos Reis (2023)
This research is part of the objectives of the Postgraduate Program in Education: Curriculum, in the New Technologies in Education Research Line of the Pontifical Catholic University of São Paulo. This study describes the context and reflects on the proposal of education as a task for the whole city and not just for the school, in a territorial and administrative region of the city of São Paulo. It is assumed that cities are not educators in themselves, quite the contrary, they miseducate their inhabitants, due to the characteristics of their distribution of benefits in given regions and their cruel inequality in other bad examples that continuously develop and become acute in their urban devices. Therefore, this research seeks to describe, investigate, diagnose and point out educability criteria for education in the city. Its specific objectives are: to describe the Pedagogical Political Project of a public school in a specific region of the city of São Paulo and the relationship between teaching and learning for the citizenship formation of students; interview cultural agents in the city who mediate between the curriculum and citizenship learning; inventory spaces of education, culture, memory and leisure existing in the neighborhood of Perus – in the city of São Paulo, which are understood as tools of educational action; highlight educational elements, in which such spaces, mediated by teaching practices, contribute to the learning process, to the fulfillment of the Pedagogical Political Project and the formation of citizenship. To achieve the objectives, this dissertation was based on the area of public policies. This is a qualitative research of the neighborhood of Perus, located in the Northwest zone of the city of São Paulo, with direct observation in loco of practices carried out by cultural collectives, social movements and by the community; semi-structured interviews with community leaders and data analysis. The results showed that, schools in an organized and articulated way with cultural collectives, social movements and residents can build a neighborhood that educates and is educated